Effectiveness of Soursop (Annona muricata) and Tobacco Leaf Extract Nicotiannna Tabacum) in Killing Aedes Aegypti Mosquito at the Salatiga Vector and Reservoir Desease Research and Development Center - Emy Wiyastuti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Hemorrhagic Fever (Dengue) is an acute fever and deadly caused by a virus transmitted by Aedes aegypti mosquito For this reason, it is necessary to develop the use of plant-based insecticides, which in addition to being inexpensive and have high toxicity. The purpose of this Research is to determine and compare the effectiveness of soursop leaf extract (Annona muricata) and tobacco leaf extract (Nicotianna tabacum) in killing Aedes aegypti mosquitoes. This research design study uses a True Experiment design. The population in this study was the Aedes Aegypti mosquitoes that had been bred using simple random sampling techniques which obtained a sample of 625 mosquitoes with 4 repetitions. Statistical analysis used was the Annova multivariate statistical test and Linear Dummy Regression. Based on the results of this study it is known that the average Aedes Aegypti mosquito mortality is greatest at 60 minutes. From the results of statistical tests show there are an effect of the effectiveness of various extra doses of Soursop soursop leaf (Annona Muricata) with tobacco leaf extract (Nicotianna tabacum) in controlling Aedes Aegypti mosquitoes (p-value = 0,000), while the variables that most influence on the death of Aedes Aegypti mosquitoes are extra soursop leaves Soursop (Annona Muricata) at a dose of 100 ppm (p-value = 0.006) and tobacco leaf extract (Nicotianna tabacum) at a dose of 150 ppm (p-value = 0.025) Soursop leaf extract (Annona Muricata) at a dose of 100 and tobacco leaf extract (Nicotianna tabacum) at a dose of 150 ppm is the most effective dose used in controlling Aedes Aegypti mosquitoes if sprayed within 60 minutes or 1 hour. So that it can be developed as a vegetable insecticide in controlling Aedes Aegypti mosquitoes